Caribbean melon production and post harvest manual - Pilgrim, Ronald (FAO/CARDI RomeIT, 2011)
Describes the best practices in all aspects of commercial melon production and post-harvest handling, utilising materials, technologies and support services that are generally available to the Caribbean producer.